The effect of nanoelectrodes number and length on enhancing the THz photomixer performance - Al-Mudhafar, Reiam; Jawad, Hussein (Iraqi Journal of Laser, 2023)
Abstract: Despite the distinct features of the continuous wave (CW) Terahertz (THz) emitter using photomixing technique, it suffers from the relatively low radiation output power. Therefore, one of effective ways to improve the photomixer emitter performance was using nanodimensions electrodes inside the optical active region of the device. Due to the nanodimension sizes and good electrical conductivity of silver nanowires (Ag-NWs), they have been exploited as THz emitter electrodes. The excited surface plasmon polariton waves (SPPs) on the surface of nanowire enhances the incident excitation signal. Therefore, the photomixer based Ag-NW compared to conventional one significantly exhibits higher THz output signal. In this work, the effect of Ag-NWs dimensions and number on the incident optical field is investigated by utilizing the Computer Simulation Technology (CST) Studio Suite. The simulation results show that increasing Ag-NWs length to SPP propagation length ratio plays a significant role on the incident field increment due to its effect on reducing the SPP propagation losses. The increment of Ag-NWs number and length in the nanoelectrodes based photomixer can contribute to increase the electric field in the active region by 1.5 times at the longer excitation wavelength (850 nm). As a result of this increment, the THz output power and the conversion efficiency are expected to be enhanced by a factor of five